Task Management System Untuk Osis - Pratiwi MN, Mega Indera; Sumarno, Alim; Roesminingsih, Erny (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Students are one of the important factors for the continuity of education in schools. Without students, school programs cannot be realized. Therefore, students need to be facilitated well so that school programs can move and successfully achieve educational goals. One of the facilities for developing student potential is the existence of an OSIS (Intra-School Student Organization). Writing articles uses the library research method. This article will reveal how the task management system can be utilized by the OSIS to manage work programs that will be carried out by joining in a system and then collaborating, coordinating, distributing tasks, and so on so that the work program can be carried out effectively and efficiently.